Ethnobotany of the Medicinal Plants Used by the Inhabitants of Guadalupe, la Libertad, Peru - Martinez-Salinas, J (MS-EDITIONS, 2025)
This study determined the medicinal flora used by the inhabitants of the district of Guadalupe, Pacasmayo, La Libertad. A total of 382 semi-structured interviews were conducted using the snowball technique. One hundred and ten medicinal species were identified, distributed among 105 genera and 51 families, with Asteraceae, Lamiaceae, Fabaceae, and Solanaceae being the most abundant. These species are used to treat 67 diseases, grouped into 12 categories, with urinary, musculoskeletal, digestive, nervous, respiratory, and cardiovascular conditions being the most commonly treated, according to the Informant Consensus Factor Index (ICFI). In addition, six species (6.6% of the total) had a high Use Value Index (IVU), demonstrating their importance to the community. The findings highlight the need to conserve these resources and promote their sustainability, contributing to the well-being of the population and local development.